2015
DOI: 10.1021/cm503864u
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Tailoring of Solid-State Order in Diketopyrrolopyrrole-Based Copolymers via Intramolecular Noncovalent Interactions

Abstract: Understanding the microstructures of semiconducting polymers is critical for improving the charge transport properties of polymer field-effect transistors (PFETs). A series of diketopyrrolopyrrole-based copolymers designed by implementing the concept of intramolecular noncovalent conformational locks through the functionalization of polymer backbones with fluorine atoms or methoxy groups were synthesized and compared with their unfunctionalized analogue. In contrast to the bimodal texture of the unfunctionaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
125
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 127 publications
(141 citation statements)
references
References 52 publications
9
125
0
Order By: Relevance
“…While a clear explanation for this change in the orientation has not yet been provided, it may be related to the change in intermolecular interactions of the polymers resulting from the change in the side chains. Reproduced with permission [90] Copyright 2015, American Chemical Society. Reproduced with permission.…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%
“…While a clear explanation for this change in the orientation has not yet been provided, it may be related to the change in intermolecular interactions of the polymers resulting from the change in the side chains. Reproduced with permission [90] Copyright 2015, American Chemical Society. Reproduced with permission.…”
Section: Wileyonlinelibrarycommentioning
confidence: 99%
“…To promote macromolecular planarity, non-covalent intramolecular interactions such as S···F and S···O interactions in conjugated polymer backbones have previously been employed. [13][14][15][16][17][18] These conjugated molecules with S···O or S···F interaction cause extended conjugation of the π-orbital due to a diminished torsion angle, which induces strong π-π stacking properties. For instance, Kim et al demonstrated that the 2,2-(2,5-difluoro-1,4phenylene)dithiophene based copolymers with S···F interaction have high alignment and vertical ordering properties in film, which induced faster field-effect hole mobility of more than three times compared to that without the S···F interaction polymer.…”
Section: 5 D-a Polymersmentioning
confidence: 99%
“…8 Very recently it has been shown that comonomers with the thiophene-phenyl-thiophene (TPT) motif are especially promising candidates to facilitate highly planar, crystalline and aggregating DPP copolymers. [8][9][10] In order to further promote the planarization of semiconducting polymers the exploitation of diffusive nonbonding heteroatom interactions has been employed. 11 Two of those interactions are the hydrogen-fluorine and the hydrogen-oxygen interactions that help lock the conformation of the polymer backbone into a more planarized state.…”
Section: Introductionmentioning
confidence: 99%
“…12 Not only fluorinated phenylene units have been shown to be valuable building blocks for semiconducting copolymers, 13 but recently it has been shown that for the TPT motif, bifluorination or bialkoxylation of the central phenyl unit facilitates charge transport and leads to either preferred edge-on alignment in the case of fluorination or face-on alignment in the case of alkoxylation. 9 On the other hand, a tetrafluorinated TPT derivative has been employed in oligomers 14,15 as well as in DPP copolymers carrying furanyl flanking units by Sonar et al 16 and has been found to provide ambipolarity in OFET devices. It is hitherto unknown whether this ambipolarity is caused by the furanyl-flanking units or the tetrafluorination of the TPT.…”
Section: Introductionmentioning
confidence: 99%